The Effect of Stimulation on the Development of the Child's Drawing Stage - Siti Alfiah; Darsinah Darsinah (International Journal Labs, 2023)
The way to learn in early childhood is through play, therefore it is necessary to know the stages of play at each age so that teachers can be mature at higher stages of play. This study aimed to determine the stages of drawing in early childhood. 1) KB (3-4 years). 2) TK A (4-5 years). 3) TK B (5-6 years). This research is a type of experiment with the design of one group of post-test pretests and data collection methods through observation. The object of study is a drawing document of children aged (3-6 years). The research was carried out in the first semester of the 2022/2023 academic year and the data was taken between September 19, 2022 - October 19, 2022, with data analysis techniques using content analysis techniques. The results of this study show that the value is 0.001 which is smaller than 0.05. This shows that stimulation significantly influences the development of the child's drawing stage.